2011
DOI: 10.1051/0004-6361/201117139
|View full text |Cite
|
Sign up to set email alerts
|

Arcsecond resolution images of the chemical structure of the low-mass protostar IRAS 16293-2422

Abstract: It remains a key challenge to establish the molecular content of different components of low-mass protostars, like their envelopes and disks, and how this depends on the evolutionary stage and/or environment of the young stars. Observations at submillimeter wavelengths provide a direct possibility to study the chemical composition of low-mass protostars through transitions probing temperatures up to a few hundred K in the gas surrounding these sources. This paper presents a large molecular line survey of the d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
179
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(195 citation statements)
references
References 33 publications
14
179
1
1
Order By: Relevance
“…Interferometric data of the HDO 3 1,2 −2 2,1 transition show that, in addition to the main emission coming from the source A, a weaker component of HDO is emitted at about 6 from core A (see Fig. 20 in Jørgensen et al 2011). The beam size of the IRAM-30 m telescope at 81 GHz encompasses this component and could explain the lack of predicted flux as well as the different line profile.…”
Section: Determination Of the Hdo Abundancementioning
confidence: 98%
See 1 more Smart Citation
“…Interferometric data of the HDO 3 1,2 −2 2,1 transition show that, in addition to the main emission coming from the source A, a weaker component of HDO is emitted at about 6 from core A (see Fig. 20 in Jørgensen et al 2011). The beam size of the IRAM-30 m telescope at 81 GHz encompasses this component and could explain the lack of predicted flux as well as the different line profile.…”
Section: Determination Of the Hdo Abundancementioning
confidence: 98%
“…As source A is more massive than source B, we considered that the structure is centered on core A. According to interferometric data of the HDO 3 1,2 −2 2,1 line at 226 GHz, deuterated water is mainly emitted by core A (Jørgensen et al 2011 Crimier et al (2010). The expected abundance profile of water is added (dashed-dotted line) on an arbitrary Y-scale.…”
Section: H 18mentioning
confidence: 99%
“…The determination of the centroid velocity toward each source is a matter of debate, where different studies present different results. While Bisschop et al (2008) argued that the high-excitation lines of the complex organics peak at V LSR = 1.5−2.5 km s −1 toward both sources, Jørgensen et al (2011) reported average systemic velocities of 3.2 and 2.7 km s −1 and average line widths of 2.6 and 1.9 km s −1 for A and B, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies (e.g., Kuan et al 2004;Bottinelli et al 2004;Rao et al 2009;Bisschop et al 2008;Crimier et al 2010;Jørgensen et al 2011) have focused on I16293 to characterize the A&A 544, L7 (2012) respective nature of the two continuum sources. Indeed, I16293 is known to have a quadrupolar outflow (Walker et al 1988;Mizuno et al 1990;Castets et al 2001;Rao et al 2009) suggesting the existence of a binary system.…”
Section: Introductionmentioning
confidence: 99%
“…The broadband capabilities of modern interferometers allow many spectral lines to be observed in a single correlator setup, enabling astronomers to simultaneously trace multiple astrophysical phenomena, or undertake unbiased line surveys to work toward complete molecular inventories (e.g., Jørgensen et al 2011;Coutens et al 2016;Müller et al 2016). Within these data sets, many scientifically interesting lines may be weak or not detected due to low column densities or intrinsically low line strengths.…”
Section: Introductionmentioning
confidence: 99%